WMO world record lightning extremes : longest reported flash distance and longest reported flash duration - Lang, Timothy J.; Pédeboy, Stéphane; Rison, William; Cerveny, Randall S.; Montanyà, Joan; Chauzy, Serge; MacGorman, Donald R.; Holle, Ronald L.; Ávila, Eldo Edgardo; Zhang, Yijun; Carbin, Gregory; Mansell, Edward R.; et al. (2025)
Fil: Lang, Timothy J. NASA. Marshall Space Flight Center; United States of America.